WOMEN SATISFACTION IN ANTENATAL CARE SERVICES - Andita Rosanah; Dian Pitaloka Priasmoro; Juliati Koesrini (Indonesian Journal Of Empirical Nursing Sciences, 2024)
Background Pregnant women's satisfaction with Antenatal Care (ANC) services has a significant impact on the quality of maternal and neonatal care. The aim of this research is to determine the description of pregnant women's satisfaction with the Antenatal Care Service at the Puri Bunda Mother and Child Hospital, Malang City. Methods This research design used quantitative research with a descriptive research design. The population in this study were all pregnant women who had an antenatal care visit at Puri Bunda Hospital, Malang in March 2023. The sampling technique used was accidental sampling with a total of 90 research respondents. Measuring tool with a questionnaire sheet to measure patient satisfaction in antenatal care services. Data analysis uses univariant analysis. Result The research results showed that patient satisfaction was 50% very satisfied and 50% satisfied. This is expected to provide an overview of pregnant women's satisfaction with Antenatal Care services at hospitals in providing antenatal care services.